Evaluating the 2026 Computer-Based Academic Ability Test in Kediri Elementary Schools: Procedural Compliance and Infrastructure Readiness - Ali Muchasan; Desy Putri P; Inchinia Angger Rowin; Joko Irianto; Sanusi (JURNAL PENDIDIKAN DASAR NUSANTARA, 2026)
The transition of primary education assessment toward Computer-Based Testing (CBT) requires not only student readiness but also procedural compliance, adequate devices, reliable internet connectivity and electricity, and sufficient technical support at the school level. Differences in capacity across educational institutions may result in unequal implementation, particularly among schools located in peripheral areas. Against this background, the research problem concerns the extent of procedural compliance and technical infrastructure readiness among elementary schools in implementing the CBT-based Academic Ability Test (Tes Kemampuan Akademik—TKA) in Kediri Regency in 2026. This study aimed to evaluate the implementation of the elementary-level TKA in relation to these two aspects. A descriptive quantitative approach was employed using a structured survey based on a monitoring instrument developed by the Kediri Regency Education Council. The study involved 22 sampled schools across 10 districts, comprising 18 public elementary schools and four private/Islamic elementary schools, with 853 registered participants. The instrument consisted of a 29-item dichotomous checklist and a five-point Likert scale covering the preparation and implementation dimensions. The findings revealed a participant attendance rate of 99.88%; all schools independently administered online CBT; checklist compliance reached 95.5%; and the mean scores for preparation, implementation, and overall performance were 4.503, 4.257, and 4.380, respectively, all of which were classified as excellent. The primary constraint was the absence of an uninterruptible power supply (UPS) or generator in four schools (18%). The study concludes that the initial implementation of the elementary-level TKA was highly successful; however, further improvements are needed in electrical infrastructure, support for schools in peripheral areas, and the institutionalization of annual monitoring.